2022
DOI: 10.1038/s41591-022-01867-3
|View full text |Cite
|
Sign up to set email alerts
|

Onasemnogene abeparvovec for presymptomatic infants with three copies of SMN2 at risk for spinal muscular atrophy: the Phase III SPR1NT trial

Abstract: Most children with biallelic SMN1 deletions and three SMN2 copies develop spinal muscular atrophy (SMA) type 2. SPR1NT (NCT03505099), a Phase III, multicenter, single-arm trial, investigated the efficacy and safety of onasemnogene abeparvovec for presymptomatic children with biallelic SMN1 mutations treated within six postnatal weeks. Of 15 children with three SMN2 copies treated before symptom onset, all stood independently before 24 months (P < 0.0001; 14 within normal developmental window), and 14 walked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
153
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 160 publications
(161 citation statements)
references
References 42 publications
6
153
0
2
Order By: Relevance
“…The following supporting information can be downloaded at: , Table S1: Model parameter and expected values with ranges for the model. References [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ] are cited in the Supplementary Materials.…”
mentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: Model parameter and expected values with ranges for the model. References [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ] are cited in the Supplementary Materials.…”
mentioning
confidence: 99%
“…The SPR1NT trial enrolled infants aged ≤ 6 weeks with pre-symptomatic SMA and two [21] or three [22] copies of SMN2 (with no c.859C→G modifier variants). Participants were able to swallow and breathe normally and had no clinical evidence of neuromuscular disease [21,22].…”
Section: Pre-symptomatic Smamentioning
confidence: 99%
“…The SPR1NT trial enrolled infants aged ≤ 6 weeks with pre-symptomatic SMA and two [21] or three [22] copies of SMN2 (with no c.859C→G modifier variants). Participants were able to swallow and breathe normally and had no clinical evidence of neuromuscular disease [21,22]. All children received a single intravenous infusion of onasemnogene abeparvovec 1.1 × 10 14 vg/kg at the median age of 21 days in the two-copy cohort [21] and 32 days in the three-copy cohort [22].…”
Section: Pre-symptomatic Smamentioning
confidence: 99%
See 1 more Smart Citation
“…4 The 15 children with three copies of SMN2 were all able to stand for at least three seconds at the age of two years and 14 were able to walk. 4,5 Adverse reactions to onasemnogene abeparvovec are common. A review of safety data from several trials identified hepatotoxicity, thrombocytopenia, and cardiac adverse events as potential problems.…”
mentioning
confidence: 99%